2008
DOI: 10.1155/2008/583470
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Endoscopic Gastrostomy in Children

Abstract: Percutaneous endoscopic gastrostomy has been a valuable tool in nutritional rehabilitation since its inception in 1980. Although it was originally described in children, a large sector of the adult population is dependent on it for nutritional support. Percutaneous endoscopic gastrostomy tube insertion is generally a safe procedure. Nevertheless, variable incidence rates of complications have been reported. The present review highlights the up-to-date indications, contraindications and complications of percuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 48 publications
5
49
0
6
Order By: Relevance
“…G astrostomy tube insertion in children can be performed via open surgery, percutaneous endoscopic gastrostomy (PEG), laparoscopic gastrostomy, or percutaneous radiologic gastrostomy. [1][2][3][4][5] Percutaneous endoscopic gastrostomy insertion remains popular in many centres because it can be performed quickly and does not require incisions. 1,2 This approach provides visualization of the stomach but not the peritoneal cavity, which can lead to injuries to the colon, small bowel, liver and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…G astrostomy tube insertion in children can be performed via open surgery, percutaneous endoscopic gastrostomy (PEG), laparoscopic gastrostomy, or percutaneous radiologic gastrostomy. [1][2][3][4][5] Percutaneous endoscopic gastrostomy insertion remains popular in many centres because it can be performed quickly and does not require incisions. 1,2 This approach provides visualization of the stomach but not the peritoneal cavity, which can lead to injuries to the colon, small bowel, liver and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…high density). El-Mantary, (45) suggested that aggressive nutritional support was essential in improving the outcome in cancer patients in catabolic states. However, it is often difficult to establish adequate oral feeding despite energy dense supplements due to the underlying malignancy, in addition to the aggressive chemo-and radiotherapy.…”
Section: Nutrition Support In the Child With Cancermentioning
confidence: 99%
“…Nasogastric and nasojejunal tubes were most frequently used for shorter term feeding whereas gastrostomy and jejunostomy feeding were suggested for longer term feeding and certain cancers in which high dose treatment was frequent and associated with vomiting. (45) Parenteral nutrition is reserved for those children whose enteral feeding regimens cannot provide adequate nutrition, in particular children with abnormal gastrointestinal function that is related either to the tumour or a side effect of treatment. (1,46) In comparison to parenteral feeding, enteral nutrition is considered to be more practical, has a lower risk of infection, maintains gut integrity and reduces the risk of bacterial translocation.…”
Section: Nutrition Support In the Child With Cancermentioning
confidence: 99%
See 2 more Smart Citations